Altering singlet fission pathways in perylene-dimers; perylene-diimide versus perylene-monoimide - Papadopoulos, Ilias; Gutierrez-Moreno, David; Bo, Yifan; Casillas, Ruben; Greißel, Phillip; Clark, Timothy; Fernandez-Lazaro, Fernando; Guldi, Dirk Michael (Nanoscale, 2022)
We used a systematic approach to shed light on the inherent differences in perylenes, namely monoimides versus diimides, including coplanarity and dipole moment, and their impact on singlet fission (SF) by designing, synthesizing, and probing a full fledged series of phenylene- and naphthalene-linked dimers. Next to changing the functionality of the perylene core, we probed the effect of the spacers and their varying degrees of rotational freedom, molecular electrostatic potentials, and intramolecular interactions on the SF-mechanism and -efficiencies. An arsenal of spectroscopic techniques revealed that for perylene-monoimides, a strong charge-transfer mixing with the singlet and triplet excited states restricts SF and yields low triplet quantum yields. This is accompanied by an up-conversion channel that includes geminate triplet-triplet recombination. Using perylene-diimides alters the SF-mechanism by populating a charge-separated-state intermediate, which either favors or shuts-down SF. Napthylene-spacers bring about higher triplet quantum yields and overall better SF-performance for all perylene-monoimides and perylene-diimides. The key to better SF-performance is rotational freedom because it facilitates the overall excited-state polarization and amplifies intramolecular interactions between chromophores.
CRIS-Team WoS Importer:2022-04-08

A Universal Design Strategy Based on NiPS3 Nanosheets towards Efficient Photothermal Conversion and Solar Desalination - Wang, Honglei; Bo, Yifan; Klingenhof, Malte; Peng, Jiali; Wang, Dong; Wu, Bing; Pezoldt, Jörg; Cheng, Pengfei; Knauer, Andrea; Hua, Weibo; Wang, Hongguang; van Aken, Peter A.; et al. (Advanced Functional Materials, 2023)
2D nanomaterials are proposed as promising photothermal materials for interfacial photothermal water evaporation. However, low evaporation efficiency, the use of hazardous hydrofluoric solution, and poor stability severely limit their practical applications. Here, a mixed solvent exfoliation surface deposition (MSESD) strategy for the preparation of NiPS3 nanosheets and NiPS3/polyvinyl alcohol (PVA) converter is successfully developed. The converter is obtained by drop-casting the NiPS3/PVA nanosheets onto a sponge. The PVA is mainly deposited on the edge of NiPS3 nanosheets, which not only improves the stability of NiPS3 nanosheets, but also adheres to the sponge to prepare a 3D photothermal converter, which shows an evaporation rate of 1.48 kg m−2 h−1 and the average photothermal conversion efficiency (PTCE) of 93.5% under a light intensity of 1 kW m−2. The photothermal conversion mechanism reveals that the energy of absorbed photons in NiPS3 nanosheets can be effectively converted into heat through non-radiative photon transitions as well as multiple optical interactions. To the best of the knowledge, this is the first report on the application of 2D metal-phosphorus-chalcogen (MPChx) for solar desalination, which provides new insights and guidance for the development of high-performance 2D photothermal materials.
CRIS-Team Scopus Importer:2023-11-17
Keywords: 2D materials; desalination; NiPS; photothermal conversions; surface depositions

Catalyzing Singlet Fission by Transition Metals: Second versus Third Row Effects - Hou, Yuxuan; Papadopoulos, Ilias; Bo, Yifan; Wollny, Anna-Sophie; Ferguson, Michael J.; Mai, Lukas; Tykwinski, Rik R.; Guldi, Dirk Michael (Precision Chemistry, 2023)
The synthesis and characterization of platinum(II) and palladium(II) complexes bearing two (dimers Pt(Lpc)2Cl2 and Pd(Lpc)2Cl2), one (monomers Pt(Lpc)(Lref)Cl2 and Pd(Lpc)(Lref)-Cl2), or no (reference compounds Pt(Lref)2Cl2 and Pd(Lref)2Cl2) pentacene-based pyridyl ligands are presented. Photophysical properties of the dimers are probed by means of steady-state and time-resolved transient absorption measurements in comparison to the monomer and model compounds. Our results document that despite enhanced spin-orbit coupling from the presence of heavy atoms, intramolecular singlet fission (iSF) is not challenged by intersystem crossing. iSF thus yields correlated triplet pairs and even uncorrelated triplet excited states upon decoherence. Importantly, significant separation of the two pentacenyl groups facilitates decoupling of the two chromophores. Furthermore, the mechanism of iSF is altered depending on the respective metal center, that is, Pt(II) versus Pd(II). The dimer based on Pt(II), Pt(Lpc)2Cl2, exhibits a direct pathway for the iSF and forms a correlated triplet pair with singlet-quintet spin-mixing within 10 ns in variable solvents. On the other hand, the dimer based on Pd(II), Pd(Lpc)2Cl2, leads to charge transfer mixing during the population of the correlated triplet pair that is dependent on solvent polarity. Moreover, Pd(Lpc)2Cl2 gives rise to a stable equilibrium between singlet and quintet correlated triplet pairs with lifetimes of up to 170 ns. Inherent differences in the size and polarizability, when contrasting platinum(II) with palladium(II), are the most likely rationale for the underlying trends.
CRIS-Team Scopus Importer:2024-12-16
Keywords: electronic coupling; metal complexes; pentacene dimers; singlet fission; ultrafast spectroscopy

Fused Hexabenzocoronene-Porphyrin Conjugates with Tailorable Excited-State Lifetimes - Oleszak, Christoph; Schol, Peter; Ritterhoff, Christian; Krug, Marcel; Martin, Max; Bo, Yifan; Meyer, Bernd; Clark, Timothy; Guldi, Dirk Michael; Jux, Norbert (Angewandte Chemie International Edition, 2024)
A new clear-cut strategy for fusing N-heterocyclic and carbon-pure systems is introduced en route to a versatile platform of multi-purpose tetrapyrrolic chromophores. In particular, three novel C−C bond-fused porphyrin-hexabenzocoronene (HBC) conjugates were synthesized under oxidative cyclodehydrogenation conditions, starting from tailor-made nickel porphyrin precursors. The fusion of the individual aromatic systems via 5-membered rings led to highly soluble π-extended porphyrins in excellent yields. The resulting porphyrin-HBC conjugates exhibit absorption cross-sections that are of interdisciplinary interest in the ever-growing field of organic photovoltaics and near-infrared (NIR) dyes. Quantum chemical calculations show that the newly formed 5-membered rings induce biradicaloid character in the porphyrin core, which has a strong impact on excited state lifetimes. This is confirmed by a thorough optoelectronic and time-resolved characterization in order to understand these unique features better. Broadened absorption characteristics go hand-in-hand with short-lived excited states with up to six orders of magnitude faster decay rates.
CRIS-Team Scopus Importer:2024-10-25
Keywords: biradicaloids; porphyrinoids; post-functionalization; Scholl oxidation; π-extension

Interfullerene Electronic Interactions and Excited-State Dynamics in Fullerene Dumbbell Conjugates - Chai, Yongqiang; Liu, Liping; Xu, Yanjun; Liu, Xiaolong; Wang, Chong; Bo, Yifan; Zhang, Yuhe; Wang, Zhuan; Weng, Yuxiang; Guldi, Dirk Michael; Wu, Bo; Wang, Chunru (Journal of the American Chemical Society, 2023)
Several dumbbell conjugates featuring M3N@Ih-C80 (M = Sc, Y) and C60 were prepared to systematically investigate interfullerene electronic interactions and excited state dynamics. From electrochemical investigations, we concluded that the redox potentials of our M3N@Ih-C80 (M = Sc, Y) dumbbells depend largely on the interfullerene electronic interactions. Assisted by DFT calculation, the unique role of metal atoms was highlighted. Most importantly, ultrafast spectroscopy experiments revealed symmetry-breaking charge separation in Sc3N@C80-dumbbell to yield an unprecedented (Sc3N@C80)•+-(Sc3N@C80)•- charge separated state. This is, to the best of our knowledge, the first time that symmetry-breaking charge separation following photoexcitation is corroborated in a fullerene system. As such, our work shed light on the significance of interfullerene electronic interactions and their uniqueness for modulating excited state properties.
CRIS-Team Scopus Importer:2023-09-29

Intramolecular Down- and Up-Conversion in Dimeric Tetracene Complexes Centered via Platinum(II) and Palladium(II) - Bo, Yifan; Hou, Yuxuan; Matabuena, Melchor; Tykwinski, Rik R.; Guldi, Dirk Michael (Advanced Functional Materials, 2025)
Two dimeric tetracene complexes, Pt(Ltc)2Cl2 and Pd(Ltc)2Cl2, have been synthesized by coordination of a pyridyl substituted acene- to a Pt(II) and Pd(II) metal center. The photophysical properties of the two dimers are characterized and compared with the free tetracene ligand Ltc, as well as the corresponding monomeric complexes (Pt(Ltc)(Lref)Cl2 and Pd(Ltc)(Lref)Cl2) to shed light on the processes of intramolecular up- and down-conversion, namely triplet-triplet annihilation and singlet fission, respectively. Both the free ligand Ltc and Pt(Ltc)(Lref)Cl2 show high fluorescence quantum yields, while emission is heavily reduced in the Pt(Ltc)2Cl2 and Pd(II) complexes. Dimer Pt(Ltc)2Cl2 exhibits efficient singlet fission within 1.6 ns to form a correlated triplet pair (T1T1), confirming that coupling is mediated through Pt(II) over remarkably long inter-chromophore distances. Subsequently, (T1T1) dissociates into free triplets (T1 + T1) with yields of ca. 50%. Moreover, due to the isoenergetic level of the singlet excited state and (T1T1) for tetracene dimers, some (T1T1) in Pt(Ltc)2Cl2 is observed to undergo intramolecular up-conversion and return to the singlet excited state, followed by upconverted fluorescence. On the other hand, photoexcitation of Pd(Ltc)2Cl2 gives a kinetic behavior that is similar to the monomer Pd(Ltc)(Lref)Cl2, namely no singlet fission but fast intersystem crossing within hundreds of picoseconds. It is noted that triplet formation in the Pd(II) monomer and dimer complexes is low, and that non-radiative decay of the singlet excitons to the ground state dominates in both cases. The singlet excited state of all metal–organic complexes exhibits subtle intrachromophore charge-transfer characteristics in polar solvents and kinetic schemes that are similar to that observed in apolar solvents.
CRIS-Team Scopus Importer:2025-05-30
Keywords: intramolecular down-conversion; intramolecular singlet fission; intramolecular up-conversion; Pt(II)/Pd(II) metal complex; tetracene dimers

Molecular Acenes for Light Capture, Conversion, and Storage - Greißel, Phillip; Wollny, Anna-Sophie; Bo, Yifan; Thiel, Dominik; Weiß, René; Guldi, Dirk Michael (Accounts of Materials Research, 2024)
Conspectus Efficient photovoltaics (PV) require capturing and converting solar energy across a broad range of energy. Losses due to thermalization and sub-bandgap photons place, however, significant boundaries on the performance of solar cells. For conventional single-junction cells, the theoretical maximum power conversion efficiency is capped at 33%, a constraint known as the detailed balance limit. Realizing the full potential of PVs requires developing novel strategies to overcome this fundamental obstacle. This Account describes the photon-management capabilities of acenes and addresses these fundamental losses en-route toward enhancing PV performances. For high-energy photons that exceed the semiconductor’s bandgap energy, singlet fission (SF) is a down-conversion pathway to mitigate thermalization losses. SF is a process in organic materials, in which a singlet excited state is split into two independent triplet excited states, effectively doubling the number of charge carriers. Pentacenes stand out among acenes due to their exergonic nature of SF. Numerous molecular pentacene dimers have been synthesized to elucidate the relationship between structure and enhancing SF efficiency. A broader light-harvesting range of SF materials is realized by covalently attaching complementary absorbing energy donors to set up energy donor-acceptor conjugates. Förster resonance energy transfer (FRET) is operative in these energy donor-acceptor conjugates, effectively extending the absorption of SF materials, as the energy donor efficiently transfers its absorbed excitation energy to the energy acceptor. Our studies on various binding motifs show that FRET efficiency depends not only on parameters like the energy donor-acceptor distance and spectral overlap but also on subtle factors such as the alignment of transition dipoles, which significantly affect the energy transfer dynamics and efficiency. Turning to low-energy photons, triplet-triplet annihilation up-conversion (TTA-UC) provides a means of light up-conversion and, thereby, the reduction of sub-bandgap losses. In TTA-UC, a singlet excited state that is potent enough to generate charge carriers is formed by combining two triplet excitons. It is effectively the reverse process of SF. The higher triplet energy of tetracene and an endergonic SF renders them highly effective for TTA-UC. We focus on various tetracene-based systems that maximize TTA-UC efficiency. Besides TTA-UC, two-photon absorption (TPA) is yet another mechanism to leverage below-bandgap photons. It is a nonlinear optical (NLO) process, and acenes reveal NLO properties that are essential for extending light absorption into the near-infrared and still powering SF. We demonstrate in our proof-of-concept studies how TPA further broadens the application potential of acenes for PV systems. The strategies outlined in this Account illustrate that acenes are valuable for addressing mechanistic losses in conventional solar cells. In the final section, we examine light storage following SF by means of interfacial electron transfer. Efficient charge-injection powered by SF materials still requires more research before being implemented in large-scale PV designs. Overall, the advances discussed in this Account not only highlight the pivotal role of acenes as model systems to investigate photon down- and up-conversion processes but also paint a promising picture that more efficient solar energy conversion schemes exceeding the detailed-balance limit can be realized by implementing these materials.
CRIS-Team Scopus Importer:2025-02-04

One-Pot Synthesis and Excited-State Dynamics of Null Exciton-Coupled Diketopyrrolopyrroles Oligo-Grids - Bo, Yifan; Hou, Pengfei; Wan, Jun; Cao, Hongtao; Liu, Yuyu; Xie, Linghai; Guldi, Dirk Michael (Advanced Materials, 2023)
Exciton coupling in molecular aggregates plays a vital role in impacting and fine-tuning optoelectronic materials and their efficiencies in devices. A versatile platform to decipher aggregation-property relationships is built around multichromophoric architectures. Here, a series of cyclic diketopyrrolopyrrole (DPP) oligomers featuring nanoscale gridarene structures and rigid bifluorenyl spacers are designed and synthesized via one-pot Friedel–Crafts reaction. DPP dimer [2]Grid and trimer [3]Grid, which are cyclic rigid nanoarchitectures of rather different sizes, are further characterized via steady-state and time-resolved absorption and fluorescence spectroscopies. They exhibit monomer-like spectroscopic signatures in the steady-state measurements, from which null exciton couplings are derived. Moreover, in an apolar solvent, high fluorescence quantum yields and excited-state dynamics that resembled DPP monomer are gathered. In a polar solvent, the localized singlet excited state on a single DPP dissociates into the adjacent null coupling DPP with charge transfer characteristics. This pathway facilitates the evolution of the symmetry-broken charge-separated state (SB-CS). Notable is the fact that the SB-CS of [2]Grid is, on one hand, in equilibrium with the singlet excited state and promotes, on the other hand, the formation of the triplet excited state with a yield of 32% via charge recombination.
CRIS-Team Scopus Importer:2023-08-11
Keywords: diketopyrrolopyrroles; null-aggregates; rigidity of molecular structures; symmetry-breaking charge separation

Reversible gating of singlet fission by tuning the role of a charge-transfer state - Bo, Yifan; Hou, Yuxuan; Lavergne, Dominic A.X.; Clark, Timothy; Ferguson, Michael J.; Tykwinski, Rik R.; Guldi, Dirk Michael (Nature Communications, 2025)
Stimulus-responsive triplet excited states and multiexcitonic logic gates have garnered increasing interest. Singlet fission is an efficient multiple exciton generation process, in which one singlet converts into two triplets. Singlet fission is, however, rarely reported to be switchable by external stimuli. Here we design a meta-diethynylphenylene-linked tetracene dimer featuring pyridyl endgroups that function as an acid/base-responsive switch, enabling the reversible modulation of singlet fission. In its neutral form, the interchromophore charge-transfer state facilitates singlet fission and promotes the formation of a correlated triplet-pair state. Upon treatment with acid, protonation of the pyridyl nitrogens generates a more strongly electron-accepting pyridinium, leading to an intra-chromophore charge-transfer state, which inhibits singlet fission. Finally, an IMPLICATION logic gate is constructed by using acid and base as inputs and monitoring the formation of triplet excited states based on singlet fission.
CRIS-Team Scopus Importer:2025-04-11

Synthesis, physicochemical properties and theoretical calculations of a subphthalocyanine peripherally substituted by multiple anthryl-ethynyl-aniline moieties - Fernandez-Vera, Oscar; Bo, Yifan; Luo, Yusen; Labella, Jorge; Guldi, Dirk Michael; Torres, Tomás; Bottari, Giovanni (Journal of Porphyrins and Phthalocyanines, 2023)
We report here the synthesis of a novel C3-subphthalocyanine (SubPc)-based electron donor-acceptor conjugate (1) in which the macrocycle has been functionalized at its peripheral positions with three anthryl-ethynyl-N,N-dimethylaniline groups. The latter moiety, besides conferring increased stability and solubility to the resulting system, substantially broadens its absorption capability. In-depth spectroscopic, spectrometric, and electrochemical analyses as well as theoretical calculations carried out on 1 suggest a moderate ground state intramolecular interaction between the macrocycle and the orthogonally-arranged anthryl-ethynyl-N,N-dimethylaniline moieties. Interestingly, such electronic communication significantly increases in the excited state in a process strongly depending on the polarity of the solvent. On the one hand, in toluene, upon photoexcitation of the anthryl-ethynyl-aniline, the formation of a 1*(SubPc) state is observed which decays into a 3*(SubPc) manifold before deactivating to the ground state. On the other hand, increasing the polarity of the solvent to tetrahydrofuran and benzonitrile, significantly modifies the fate of the photoexcited state. In this new scenario, the 1*(SubPc) state, formed directly upon 550 nm light stimulation or by 1*(anthryl-ethynyl-aniline) sensitization upon 405 nm excitation, transforms into a charge transfer (SubPc)d–-anthryl-ethynyl-anilined+ state which further evolves into a fully charge-separated (SubPc)•−-anthryl-ethynyl-aniline•+ species before deactivating to the ground state.
CRIS-Team Scopus Importer:2023-12-22
Keywords: aniline; anthryl moiety; panchromaticity; photophysics; subphthalocyanine

Tetracene Dimers: A Platform for Intramolecular Down- and Up-conversion - Bo, Yifan; Hou, Yuxuan; Thiel, Dominik; Weiß, René; Clark, Timothy; Ferguson, Michael J.; Tykwinski, Rik R.; Guldi, Dirk Michael (Journal of the American Chemical Society, 2023)
Photon energy conversion can be accomplished in many different ways, including the two opposing manners, down-conversion (i.e., singlet fission, SF) and up-conversion (i.e., triplet-triplet annihilation up-conversion, TTA-UC). Both processes have the potential to help overcome the detailed balance limit of single-junction solar cells. Tetracene, in which the energies of the lowest singlet excited state and twice the triplet excited state are comparable, exhibits both down- and up-conversion. Here, we have designed meta-diethynylphenylene- and 1,3-diethynyladamantyl-linked tetracene dimers, which feature different electronic coupling, to characterize the interplay between intramolecular SF (intra-SF) and intramolecular TTA-UC (intra-TTA-UC) via steady-state and time-resolved absorption and fluorescence spectroscopy. Furthermore, we have used Pd-phthalocyanine as a sensitizer to enable intra-TTA-UC in the two dimers via indirect photoexcitation in the near-infrared part of the solar spectrum. The work is rounded off by temperature-dependent measurements, which outline key aspects of how thermal effects impact intra-SF and intra-TTA-UC in different dimers.
CRIS-Team Scopus Importer:2023-10-06

Tuning the Absorption, Fluorescence, Intramolecular Charge Transfer, and Intersystem Crossing in Spiro[fluorene]acridinone - Bo, Yifan; Zhang, He; Li, Yue; Reva, Yana; Xie, Linghai; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2024)
In this work, we prepared a series of electron donor-acceptor systems based on spiro[fluorene-9,7’-dibenzo[c,h]acridine]-5’-one (SFDBAO). Our SFDBAOs consist of orthogonally positioned fluorenes and aromatic ketones. By fine-tuning the substitution of electron-donating pyrenes, the complex interplay among different excited-state decay channels and the overall impact of solvents on these decay channels were uncovered. Placing pyrene, for example, at the aromatic ketones resulted in a profound solvatochromism in the form of a bright charge-transfer (CT) emission spanning from yellow to red-NIR. In contrast, a dark non-emissive CT was noted upon pyrene substitution at the fluorenes. In apolar solvents, efficient triplet-excited state generation was observed for all SFDBAOs. Either charge transfer was concluded to mediate the intersystem crossing (ISC) in the case of pyrene substitution or the El-Sayed rule was applicable when lacking pyrene substitution as in the case of SFABAO. In polar solvents, charge separation is the sole decay upon pyrene substitution. Moreover, competition between ISC and CT lowered the triplet-excited state generation in SFDBAO.
CRIS-Team Scopus Importer:2024-03-22
Keywords: charge transfer; intersystem crossing; ketones; spiro-conjugation; triplet sensitizers

Understanding the Visible Absorption of Electron Accepting and Donating CNDs - Reva, Yana; Jana, Bikash; Langford, Daniel; Kinzelmann, Marina; Bo, Yifan; Schol, Peter; Scharl, Tobias; Zhao, Xinyi; Crisp, Ryan; Drewello, Thomas; Clark, Timothy; Cadranel, Alejandro; et al. (Small, 2023)
Carbon nanodots (CNDs) synthesized from citric acid and formyl derivatives, that is, formamide, urea, or N-methylformamide, stand out through their broad-range visible-light absorbance and extraordinary photostability. Despite their potential, their use has thus far been limited to imaging research. This work has now investigated the link between CNDs’ photochemical properties and their chemical structure. Electron-rich, yellow carbon nanodots (yCNDs) are obtained with in situ addition of NaOH during the synthesis, whereas otherwise electron-poor, red carbon nanodots (rCNDs) are obtained. These properties originate from the reduced and oxidized dimer of citrazinic acid within the matrix of yCNDs and rCNDs, respectively. Remarkably, yCNDs deposited on TiO2 give a 30% higher photocurrent density of 0.7 mA cm−2 at +0.3 V versus Ag/AgCl under Xe-lamp irradiation (450 nm long-pass filter, 100 mW cm−2) than rCNDs. The difference in overall photoelectric performance is due to fundamentally different charge-transfer mechanisms. These depend on either the electron-accepting or the electron-donating nature of the CNDs, as is evident from photoelectrochemical tests with TiO2 and NiO and time-resolved spectroscopic measurements.
Created from Fastlane, Scopus look-up
Keywords: carbon nanodots; excited state; photoelectrochemistry; semiconductors; time-resolved spectroscopy